Perancangan Sistem Informasi Pengadaan Suku Cadang Kereta Api Berbasis Web - Muhammad Ajid Duhari; Heri Wahyudi; Eko Arief Nugroho (Center of Research, STIE Pasundan, Bandung, Indonesia., 2022)
Kereta Api Indonesia DAOP (Operation Area) II Bandung is one of the operating areas of Indonesian railways, under the environment of PT Kereta Api Indonesia (Persero) which is under the Board of Directors of PT Kereta Api Indonesia led by a Head of Operations Area (Kadaop) who is under and is responsible to the Board of Directors of PT Kereta Api Indonesia. Operational Area II Bandung has three major stations, including Bandung station, Kiaracondong station, and Tasikmalaya station, while the middle class train stations include Padalarang station, Cipeundeuy station, Ciamis station, and Banjar station. The train warehouse is located at Bandung station, while the locomotive depot is not far from Bandung station. In presenting logistics information, it is still not optimal because it still uses manual methods so that in terms of time it is not effective and efficient. To solve this problem, a Web-based monitoring information system was created. The theoretical basis refers to the definition of Information Systems, Scout Movement and web builder applications including Web Browsers, Web Servers and Web editors.With the existence of an information system that supports it is expected that the processing of spare parts data and other reports can be more effective, efficient and timely.Hopefully the system created can be used as the beginning of developing a better system and can help with logistics work, so that the author hopes that employees are open to information systems that can make their work easier which may change in the future. Keywords : System, information, deposit, daily, web, responsive web